Toxic Effect of Robusta Coffee Extract (Coffea canephora) on Bali Cattle Spermatozoa After Equilibration - Fiqih, Adam Fahmi; Soeharsono, Soeharsono; Plumeriastuti, Hani; Yunita, Maya Nurwartanti; Dhamayanti, Yeni; Yudhana, Aditya (Universitas Airlangga, 2021)
The aim of this study was examine the effect of robusta coffee in bali cattle semen. A total of six cattles cement were given four treatments each P0 without adding Robusta coffee extract, P1 was given an additional 5%, P2 10%, and P3 15%. The results are observed by assessing motility, viability, and abnormalities. The data obtained were analyzed by Analysis of Variance (ANOVA) and continued with the duncan. Based on the analysis of variance in obtaining the results of the study, it was shown motility of P0 was significantly different from P1, P2, and P3 (p<0.05). Viability of P0 (control) different significantly from P1 , P2, and P3 (p<0.05). P3 motility different significantly from P0, P1, and P2 (p<0.05). Addition of robusta coffee extract of 10% and 15% decreased spermatozoa quality.